Drug-Coated Balloons Applications in Interventional Cardiology - Rigatelli, Gianluca; Zuin, Marco (Current Pharmaceutical Design, 2018)
Backgrounds: Drug coated balloons (DCBs) are new on stented-based anti-proliferative drug delivery systems, recently introduced in interventional cardiology. Their primary aim is to transfer an anti-proliferative drug to reduce the subsequent neo-intima hyperplasia and to maintain the normal vessel diameter and function. Methods: A review of the most recent influential studies about DCBs in all the fields of interventional cardiology has been performed. Results: As demonstrated by different studies, DCBs have different theoretical advantages over Drug Eluting Stents (DESs), especially for the treatment of some endovascular lesions, as In-Stent Restenosis (ISR), coronary bifurcations, small vessels disease and peripheral artery disease at femoropopliteal and below the knee sites. Conclusion: Despite the need of further studies are needed to elucidate the optimal use of DCBs their current use in interventional cardiology appears promising.
Keywords: drug